Algumas compara??es do desempenho das redes RPR e EPON como solu??es de redes de acesso - Rende, Ricarda Carolina (2007)
ABSTRACT: Ethernet Passive Optical Network (EPON) and Resilient Packet Ring (RPR) are two important technologies used as solution to the last mile access network. EPON consists of an OLT (Optical Line Terminal) and a set of ONUs (Optical Network Units) connected through star topology. RPR networks use a dual ring topology to establish the communication between end users and the central office. EPON networks are characterized for their simplicity and strong dependency on the bandwidth allocation algorithm while RPR for robustness. This thesis compares RPR and EPON networks using different bandwidth allocation methods presented in the literature. In addition, it is proposed a new bandwidth allocation algorithm for EPON networks, called CCS-DBA (Common Channel Signaling on Dynamic Bandwidth allocation). The simulation model was developed to both networks, using a discrete event simulation tool called ARENA. The average queue length and the average packet delay were analyzed through the increase of the traffic load. Keywords: EPON; RPR; traffic analysis; CCS-DBA algorithm.